1992
DOI: 10.1007/bf01575857
|View full text |Cite
|
Sign up to set email alerts
|

Restriction polymorphisms in the internal transcribed spacers and 5.8S rDNA ofSaccharomyces

Abstract: Polymorphisms in enzymatically amplified ribosomal DNA (rDNA) were examined in 18 strains of Saccharomyces. Restriction patterns generated from the region spanning the internal transcribed spacers (ITS) and the 5.8S rDNA produced two clusters corresponding to S. bayanus and S. cerevisiae. The type culture of S. carlsbergensis (ATCC 76529), which could not be separated from the S. cerevisiae group by small subunit (SSU) rDNA patterns, showed a ScrfI profile that was distinct from all the other strains. The type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…A fragment with the size of 855 bp was formed in all strains (Table 3). Molina et al (1992) found that the size of the PCR product with primers complementary to the ITS region in the species S. cerevisiae, S. bayanus and S. pastoriunus is approximately 850 bp, while the S. kluyveri (currently Lachancea kluyveri) provides a fragment of about 700 bp. Restriction analysis of the ITS region using enzymes has been performed to distinguish between species (Valente et al, 1996;Pham et al, 2011).…”
Section: ■ ■ 3 Results and Discussionmentioning
confidence: 99%
“…A fragment with the size of 855 bp was formed in all strains (Table 3). Molina et al (1992) found that the size of the PCR product with primers complementary to the ITS region in the species S. cerevisiae, S. bayanus and S. pastoriunus is approximately 850 bp, while the S. kluyveri (currently Lachancea kluyveri) provides a fragment of about 700 bp. Restriction analysis of the ITS region using enzymes has been performed to distinguish between species (Valente et al, 1996;Pham et al, 2011).…”
Section: ■ ■ 3 Results and Discussionmentioning
confidence: 99%
“…Furthermore, the 900-base sequences from S. pastonanus and S. bayanus were identical, and those from S. cerevisiae and S. paradoxus differed in only five nucleotides. rDNA restriction analysis from PCR-amplified fragments (13,(23)(24)(25) has also been used recently to differentiate between strains belonging to S. cerevisiae, S. bayanus, and S. pastorianus.…”
Section: Discussionmentioning
confidence: 99%
“…These include DNA fingerprinting (5,(31)(32)(33)(34)42), chromosomal DNA profiles (7,9,14,15,21,27), mitochondrial DNA (mtDNA) restriction analysis (22,48), and rRNA and ribosomal DNA (rDNA) sequencing (18) as well as restriction analysis (13,(23)(24)(25). Until now, only electrophoretic karyotyping, rRNA sequencing and rDNA restriction analysis have proved useful for differentiating Saccharomyces species.…”
mentioning
confidence: 99%
“…The generic term ITS represents the rDNA sequences ITS1, 5.8S, and ITS2, amplified together in the polymerase chain reaction (PCR) experiments (White et al, 1990 and Orilio Leoncini* within a species and could be used as an exclusionary characteristic for detecting misidentified isolates (Valente et al, 1996(Valente et al, , 1997, but it alone cannot identify the isolate at the species level because more than one species can have the same ITS product length. A restriction analysis of this product has already been used for black yeast and Saccharomyces identification (Molina et al, 1992;Uijthof and de Hoog, 1995;Yurlova et al, 1996) and seems to be a useful tool for differentiating phenotypically similar species that have ITS products of about the same size.…”
mentioning
confidence: 99%